SNP discovery and genotyping using restriction‐site‐associated DNA sequencing in chickens. (15th January 2015) - Zhai, Zhengxiao; Zhao, Wenjing; He, Chuan; Yang, Kaixuan; Tang, Linlin; Liu, Shuyun; Zhang, Yan; Huang, Qizhong; Meng, He
Summary Single nucleotide polymorphisms (SNPs) are essential to the understanding of population genetic variation and diversity. Here, we performed restriction‐site‐associated DNA sequencing (RAD‐seq) on 72 individuals from 13 Chinese indigenous and three introduced chicken breeds. A total of 620 million reads were obtained using an Illumina Hiseq2000 sequencer. An average of 75 587 SNPs were identified from each individual. Further filtering strictly validated 28 895 SNPs candidates for all populations. When compared with the NCBI dbSNP (chicken_9031), 15 404 SNPs were new discoveries. In this study, RAD‐seq was performed for the first time on chickens, implicating the remarkable effectiveness and potential applications on genetic analysis and breeding technique for whole‐genome selection in chicken and other agricultural animals.